(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Chukanova S. O. The Information Science as a constituent part of Library and Information Science discipline during professional training at higher educational establishments in the USA. The article is dedicated to the importance of Information Science as a part of Library and Information Science educational discipline in the USA.